Learning pathways: Levelling, scaffolding & mapping curriculum. - Reekie, Manuela; de Bosch Kemper, Nicole; Epp, Sheila; Denison, Jacqueline; Willson, Melanie; Moralejo, Lisa (Journal of Professional Nursing, 2023)
At one mid-sized research-intensive university in Western Canada, the Bachelor of Science in Nursing (BSN) program recently underwent significant curriculum revisions (Epp et al., 2021). A constructivist approach was adopted to create opportunities for students to align knowledge, skills, and abilities (KSA) with prior learning to build a deeper understanding (Vygotsky, 1978). In congruence with constructivist theory, faculty developed several learning pathways as curriculum planning tools to strategically sequence student learning outcomes, facilitate student achievement of program learning outcomes, and improve curriculum integrity. The faculty developed a conceptual model of a learning pathway and identified several key program outcomes that would benefit from a curriculum review to ensure these concepts were adequately covered across the nursing program. Each learning pathway details curriculum mapping of the levelling and scaffolding of specific concepts and content to facilitate students in the acquisition of KSA through a progressive approach (Gazza & Hunker, 2012; Maguire, 2013). This article will profile the BSN Scholarly Writing Pathway and the BSN Psychomotor Pathway as exemplars. • Learning pathways provide a framework for mapping curriculum concepts. • Learning pathways guide course development and support curriculum integrity. • Learning pathways strategically sequence student learning outcomes. • Constructivism underpins the approach of levelling and scaffolding of competencies.